PKM PELATIHAN PENGGUNAAN ALAT PERAGA IPA BAGI GURU SD DI KABUPATEN BARRU - Muhammad Amran Amir; Adnan,K Adnan,K (JA (Jurnal Abdiku) : Jurnal Pengabdian Kepada Masyarakat, 2022)
The partner of this Community Partnership Program (PKM) is the Principal of SD Inpres Padaelo, Tanete Rilau District, Barru Regency. The problem is the ability of elementary school teachers to carry out science learning activities using teaching aids is still low. The target of the activity is elementary school teachers in cluster 1, Tanete Rilau sub-district, Barru Regency. The methods used are: lecture, e-mail, discussion, and practice. The results achieved are 1) participants have understood science learning, 2) participants have understood the steps for using science teaching aids in learning, 3) participants have been able to carry out learning using science teaching aids with the help of the science kit.